Synthesis and properties of new metal complexes containing heterocyclic moieties and investigation of the role of the metal in carbon dioxide gas capture - Rawnaq Jima’a; Naser Shaalan; Muna Bufaroosha; Gamal A. El-Hiti; Benson M. Kariuki; Dina S. Ahmed; Eamd Yousif (Zaštita Materijala)
The continuous release of carbon dioxide (CO2) into the atmosphere will inevitably lead to greater environmental damage. The capture and storage of CO2 is one strategy to mitigate the harm associated with its high concentrations in the atmosphere. The design and synthesis of new materials to act as storage media for CO2 is currently an important challenge for researchers. In this regard, the investigation into the synthesis of new organometallic materials and their potential as CO2 storage media is reported. Therefore, the current work aimed to produce new materials using a simple procedure and investigate their properties, including factors affecting their CO2 adsorption. Four metal complexes containing heterocyclic units were synthesized using a simple method, and their structures were confirmed using several techniques. The surface morphology of the materials was inspected by microscopy. The metal complexes exhibited tunable particle sizes with diameters that ranged from 16.77 to 97.62 nm and a Brunauer‒Emmett‒Teller surface area of 1.20–4.01 m2/g. The materials can capture CO2 at 323 K and 40 bars, with the manganese-containing complex showing the highest CO2 storage capacity (13.1 cm3/gm).